Endoscopic Repair of a Colonic Perforation following Polypectomy Using an Endoclip - Sonny S Dhalla (Canadian Journal of Gastroenterology)
Endoscopic repair using an endoclip device for colonic perforation following polypectomy is described. This is the first case report of a repair following a regular polypectomy-induced perforation described in the English literature.